2017
DOI: 10.1080/21645515.2016.1277847
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of non-vaccination and incomplete vaccination in Canadian toddlers

Abstract: Vaccination coverage remains suboptimal in Canada and sporadic outbreaks of vaccine-preventable diseases such as measles and pertussis continue to occur. This study was undertaken to identify sociodemographic determinants of total non-vaccination (having never received any vaccine), non-vaccination for measles (0 doses) and incomplete vaccination for pertussis (< 4 doses) among 2-year-old Canadian children. Data from the 2013 Childhood National Immunization Coverage Survey (CNICS) were used. Associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 14 publications
6
67
1
2
Order By: Relevance
“…These results are in accordance with previous studies. 18,25,[32][33][34][35][36] The results of the multivariate regression analysis showed that vaccine hesitancy was more likely among parents who were worried about the side effects and safety of the vaccines. Thus, these findings highlight the need to develop educational materials promoting vaccinations and also suggest that health care workers are encouraged to inform the parents about the childhood vaccine's importance to potentially increase parental knowledge regarding the safety of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with previous studies. 18,25,[32][33][34][35][36] The results of the multivariate regression analysis showed that vaccine hesitancy was more likely among parents who were worried about the side effects and safety of the vaccines. Thus, these findings highlight the need to develop educational materials promoting vaccinations and also suggest that health care workers are encouraged to inform the parents about the childhood vaccine's importance to potentially increase parental knowledge regarding the safety of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…This subpopulation was also shown as more likely to be incompletely vaccinated against pertussis in a separate analysis conducted using the same survey data. 17 One of the plausible explanations for this finding is that the routine vaccination schedule for infants can be different in the child's country of origin. For instance, the first dose of monovalent measles vaccine is routinely recommended at nine months of age in several African, Eastern Mediterranean, South East Asian and Western Pacific countries 19 and in our analysis, doses given prior to 12 months of age were considered invalid and second doses received after 12 months of age would have been considered delayed, which was the case for only 4% children, who were not all born outside Canada.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 16 In Canada in 2013, no written proof of a dose of measles-containing vaccine was found in 10.3% (95% CI 8.9–11.6) of two-year-old children. 17 Sporadic outbreaks of measles still occur in Canada and the majority of the recent pediatric cases were unvaccinated. 18 Delayed vaccination may contribute to under-immunization in children, but the extent of delayed measles vaccination in two-year-old children in Canada is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, we were the first to identify an interaction between location of residence and income, where income effected the odds of someone living in a rural area getting vaccinated. Canada sees similar socioeconomic disparities in vaccine uptake in other publicly available vaccines, including pertussis 29. Specifically, Gilbert et al 29 found lower income household, parents with lower education and children born out of Canada had higher odds of being partially immunised for pertussis 29.…”
Section: Discussionmentioning
confidence: 96%
“…Canada sees similar socioeconomic disparities in vaccine uptake in other publicly available vaccines, including pertussis 29. Specifically, Gilbert et al 29 found lower income household, parents with lower education and children born out of Canada had higher odds of being partially immunised for pertussis 29. The low rotavirus vaccination rate in those with lower-income rural communities is particularly concerning as this population is at a higher risk of gastrointestinal illness 30.…”
Section: Discussionmentioning
confidence: 98%